2020
DOI: 10.1038/s41598-020-73298-4
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of depression-like behavior in a cystic fibrosis mouse model by Hdac6 depletion

Abstract: Cystic fibrosis (CF) patients experience heightened levels of anxiety and depression. Stress from dealing with chronic disease and rigorous treatment regimens certainly are primary contributors to these outcomes. We previously have demonstrated that microtubule alterations in CF are linked to a number of CF phenotypes including growth regulation and inflammatory responses to airway bacterial challenge. Deletion of histone deactelyase 6 (HDAC6), a cytosolic deacetylase that regulates tubulin acetylation, in CF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…This study was confirmed by [ 78 ], in which CF (cystic fibrosis) mice with a deletion of HDAC6 restored wild-type growth and inflammatory phenotype. Moreover, decreased levels of HDAC6 impacted mice behavior such that they exhibited anti-depressive properties in the tail suspension test [ 78 ]. Our study showed elevated HDAC6 in the Hp of mice subjected to CRS with a decrease in the PFC.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This study was confirmed by [ 78 ], in which CF (cystic fibrosis) mice with a deletion of HDAC6 restored wild-type growth and inflammatory phenotype. Moreover, decreased levels of HDAC6 impacted mice behavior such that they exhibited anti-depressive properties in the tail suspension test [ 78 ]. Our study showed elevated HDAC6 in the Hp of mice subjected to CRS with a decrease in the PFC.…”
Section: Discussionsupporting
confidence: 60%
“…Fukada et al (2012) found that Hdac6 deficient mice exhibit less anxiety in the EPM test and antidepressant-like behavior in the TST, while administration of the Hdac6-specific inhibitor replicated antidepressant-like behavior in mice [77]. This study was confirmed by [78], in which CF (cystic fibrosis) mice with a deletion of HDAC6 restored wild-type growth and inflammatory phenotype. Moreover, decreased levels of HDAC6 impacted mice behavior such that they exhibited anti-depressive properties in the tail suspension test [78].…”
Section: Discussionmentioning
confidence: 79%
“…Inhibiting the expression of HDAC6 enables the restoration of tubulin acetylation to normal levels in CF cells ( 175 ) and reversal of the growth defects such as height and weight caused by CF ( 176 ). Depletion of HDAC6 in CF mouse models can also regain the growth and responsive activity to bacterial challenge and inflammatory phenotypes of wild-type mice ( 31 , 177 ). Moreover, in HEK293 cells, inhibition of HDAC6 by suberoylanilide hydroxamic acid (SAHA) regulated both innate and adaptive immune responses of CF-lung disease-associated pathogenesis and progression ( 178 ).…”
Section: Histone Modifications In Inflammatory Diseasesmentioning
confidence: 99%
“…Abnormal upregulation of HDAC6 expression can also decrease β -catenin signaling, thereby inhibiting cell proliferation and migration [ 31 ]. In addition, HDAC6 upregulation can inhibit the mesenchymal transformation of hepatocellular carcinoma (HCC) epithelial cells by increasing the level of E-cadherin protein and reducing the levels of N-cadherin, vimentin, and MMP-9 proteins [ 32 ]. Notably, HDAC6 activity also correlates with emotional state and immune function.…”
Section: Discussionmentioning
confidence: 99%